Uranium incorporation biokinetics in poultry bones as function of phytase doses - Arruda-Neto, JDT; Cestari, A. C.; Zamboni, C. B.; Saiki, M.; Nogueira, G. P.; Fonseca, LEC; Manso-Guevara, M. V.; Deppman, A.; Likhachev, V. P.; Mesa, J.; Helene, OAM; Jorge, SAC; et al. (Springer, 2005)
Neutron activation analysis has been used to study uranium incorporation in poultry bones as function of chow doped with : (a) uranium (20 ppm); (b) U-doped food (20 ppm) plus phytase (120 ppm) and (c) U-doped food (20 ppm) plus phytase (180 ppm). To investigate this situation experiments involving several groups of Cobb broilers was performed. Two animals per group were sacrificed weekly up to their adultness and uranium concentration in the tibia was measured. It was observed that the concentration of uranium (mug U/g bone) is decreasing all along the animal life spanning period of 14-42 days. This behavior suggests that the skeleton mass is growing faster than the corresponding accumulation of uranium. The administration of phytase seems not to alter this scenario.